Plantain Peel Mediated Green Synthesis Iron Oxide Nanoparticles, Surface Functionalization, and Them Performance towards Methylene Blue and Methyl Orange Dye Removal - Giun Tan, Woan; Ming Ng, Wei; Kang Lim, Jit; Xin Che, Hui (International Journal of Engineering and Technology, 2018)
Currently, green synthesis approach is used as the biocompatible, eco-friendly, and sustainable alternative of conventional approaches to synthesize iron oxide nanoparticles. In this work, magnetic iron oxide nanoparticles were synthesized by using plantain peel extract via green and biogenic approach. The surface of green synthesized iron oxide nanoparticles was functionalized to increase the stability of the nanoparticles and maintain the coexisting of both magnetic and catalytic property of the nanoparticles at the same time. Two kinds of surface functionalization structures were synthesized in this study, included silica core-iron oxide shell nanoparticles and silica core-PDDA polymerized iron oxide shell nanoparticles. The main concern of this study is the performance of bare and surface functionalized green synthesized nanoparticles. Methylene blue and methyl orange dyes were used as the model of dye removal test to indicate the feasibility of the synthesized nanocomposites. In summary, surface functionalized nanocomposites achieved higher dye removal efficiency than bare green synthesized iron oxide nanoparticles in both the methylene blue and methyl orange degradation test. Methylene blue dye was removed in higher rate than methyl orange dye due to the presence of negatively charged iron oxide nanoparticles with both the adsorptive and catalytic properties. At last, the components present in plantain peel extract were confirmed by using Fourier Transform Infrared Spectroscopy.Â Â